Desarrollo de un algoritmo de selección de pozos candidatos para control de producción de agua mediante un análisis multicriterio en un campo colombiano (2019)
By means of the present work, a qualitative and quantitative analysis of a sample of five producing wells of a Colombian field was carried out, which present a significant water production, determining the degree of affectation in the profitability of hydrocarbon extraction by means of the evaluation of the behavior historical production of oil, water production, BSW, the Water-Oil Ratio (RAP) and the production of total fluid. The evaluation is done through the use of an algorithm designed by the authors of the present project, with the use of the integral application of visual basic for the programming in excel based on the multicriteria analysis REGIME through a matrix of experts.